2018
DOI: 10.1021/acs.molpharmaceut.7b00904
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Active Targeting of Melanin Granules after Intravenous Injection of Dendronized Nanoparticles

Abstract: The biodistribution of dendronized iron oxides, NPs10@D1_DOTAGA and melanin-targeting NPs10@D1_ICF_DOTAGA, was studied in vivo using magnetic resonance imaging (MRI) and planar scintigraphy through [Lu]Lu-radiolabeling. MRI experiments showed high contrast power of both dendronized nanoparticles (DPs) and hepatobiliary and urinary excretions. Little tumor uptake could be highlighted after intravenous injection probably as a consequence of the negatively charged DOTAGA-derivatized shell, which reduces the diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…At present the main clinical application of ex vivo CM in dermatology is the intraoperative control of surgical margins of cutaneous tumours, as an alternative to the traditional optical microscopy examination of frozen sections or paraffin stained with H&E. In a recent study in Mohs surgery with a new-generation scanning multimodal confocal microscope, P erez-Anker et al reported a mean scanning time of 7 min (range 3-15). 23 In a recent study with an FCM device with different samples from punch biopsies from Mohs specimens, Peters et al reported a median total time to generate and evaluate a Basal cell carcinoma, 24,[43][44][45][46][47] squamous cell carcinoma, 26,45,[48][49][50] dermatofibrosarcoma, 41 melanocytic lesions, 35,51,52,[54][55][56]77 tumours in special sites 55,62,78 (eyelid tumours, tumours of the conjunctiva, tumours of the nails) Other tumours: breast, prostate, brain, thyroid, oesophagus, stomach, colon, lung, lymph node, cervix, oral mucosa and larynx [69][70][71][72] Diagnosis of infections: mucormycosis, 63 dermatophytosis, 64 herpes virus, 65 molluscum contagiousm, 66 aspergillosis 79 Inflammatory skin diseases 36,37,68 (vasculitis, bullous diseases, psoriasis, lichen planus, discoid lupus erythematosus) Skin fillers 67 confocal laser scanning microscopy (CLSM) image of 5Á17 min (range 2Á05-20Á17). 34 Most of the ex vivo CM studies were conducted on BCCs.…”
Section: Ex Vivo Confocal Microscopy For the Evaluation Of Resection mentioning
confidence: 99%
“…At present the main clinical application of ex vivo CM in dermatology is the intraoperative control of surgical margins of cutaneous tumours, as an alternative to the traditional optical microscopy examination of frozen sections or paraffin stained with H&E. In a recent study in Mohs surgery with a new-generation scanning multimodal confocal microscope, P erez-Anker et al reported a mean scanning time of 7 min (range 3-15). 23 In a recent study with an FCM device with different samples from punch biopsies from Mohs specimens, Peters et al reported a median total time to generate and evaluate a Basal cell carcinoma, 24,[43][44][45][46][47] squamous cell carcinoma, 26,45,[48][49][50] dermatofibrosarcoma, 41 melanocytic lesions, 35,51,52,[54][55][56]77 tumours in special sites 55,62,78 (eyelid tumours, tumours of the conjunctiva, tumours of the nails) Other tumours: breast, prostate, brain, thyroid, oesophagus, stomach, colon, lung, lymph node, cervix, oral mucosa and larynx [69][70][71][72] Diagnosis of infections: mucormycosis, 63 dermatophytosis, 64 herpes virus, 65 molluscum contagiousm, 66 aspergillosis 79 Inflammatory skin diseases 36,37,68 (vasculitis, bullous diseases, psoriasis, lichen planus, discoid lupus erythematosus) Skin fillers 67 confocal laser scanning microscopy (CLSM) image of 5Á17 min (range 2Á05-20Á17). 34 Most of the ex vivo CM studies were conducted on BCCs.…”
Section: Ex Vivo Confocal Microscopy For the Evaluation Of Resection mentioning
confidence: 99%
“…However, fluorescence could improve MM identification using fusion imaging of the new EVCM device that can merge reflectance and fluorescence signals or using fluorescent-labeled antibodies. [12,14] 4.3 | EVCM for the identification of the tumor margins of MM Our study showed a good EVCM rate of correct identification of the tumor margins with only one false-positive and one false-negative result. EVCM allows an exhaustive examination of the margins of the tumor as MMS procedure.…”
Section: Evcm Feasibility For MM Imagingmentioning
confidence: 71%
“…EVCM has been mainly developed to evaluate cutaneous tumor margins, in realtime, directly on freshly excised tissue in a perioperative setting as a fast alternative to frozen histopathology during Mohs micrographic surgery (MMS) [8][9][10]. Although it has been demonstrated that the EVCM can image MM [11][12][13][14][15], its role in the definition of surgical margins has been investigated only in cutaneous carcinomas [8,10,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Following its successful application in the perioperative evaluation of malignant skin lesions as a conjunctive method for Mohs microscopic surgery , possible new indications for ex vivo CLSM have been investigated. Recent studies examining melanoma and basal cell carcinoma with ex vivo CLSM using fluorescent‐bound antibodies showed a possible application of ex vivo CLSM for immunohistochemical/immunofluorescent detection of selected cells through demonstration of specific antigen‐antibody binding in the tissue offering an alternative method to conventional fluorescence detection systems in dermatology .…”
Section: Discussionmentioning
confidence: 99%